P-149 Make the First Visit Count: Health Literacy and Counselling Should Occur During the Initial IBD Encounter. (February 2017) - Davis, Emily; Taneja, Sonia; Khan, Ali; Piech, Gregory; Alsager, Mohammed; Borum, Marie
Abstract : Background: Effective delivery of medical information requires that physicians assess patients' health literacy and adjust communication to meet literacy level. Individuals with low health literacy can have difficulty understanding the disease complexity and treatment. It is critical that patients with inflammatory bowel disease (IBD) understand their disease to make informed health care decisions. The initial health encounter can establish the physician and patient communication pattern. This study evaluated the frequency of health literacy assessment and counseling in IBD patients during the initial appointment at an IBD clinic. Methods: A retrospective chart review was performed of the initial visit of all IBD patients seen in a gastroenterology practice at a university medical center during a 6 month period. There were no exclusion criteria. Patient gender, ethnicity and disease type were obtained. Charts were assessed for counselling and performance of a health literacy assessment. Counselling was considered performed if there was documentation that the physician provided medical information regarding the disease process and management options. Health literacy was considered performed if there was documentation indicating that the patient understood the medical information provided. A database was created maintaining patient confidentiality. Statistical analysis was conducted using the Fisher Exact Test, with significance set at P < 0.05. The study was approved by the university Institutional Review Board. Results: Sixty-four patients had their initial visit to the gastroenterology clinic during the 6 month study period. There were 46 women and 18 men, with a mean age of 43.6 years. Fifteen patients had Crohn's disease (6 women, 9 men), 48 patients had ulcerative colitis (40 women, 8 men) and 1 male patient had indeterminate colitis. There were 32 Caucasians, 21 African-Americans, 2 Hispanics, 2 Asians, and 7 of other or undocumented ethnicity. Thirty-nine charts (60.9%) contained documentation of patient counselling and 17 (26.6%) had documentation of a health literacy assessment. There was a significant difference ( P = 0.0002) in the rate of counselling and health literacy assessment during the initial visit to the IBD clinic. There was no significant difference in the rate of counselling and health literacy assessment based upon gender, disease type or ethnicity. Conclusions: Health literacy is vital for the successful management of inflammatory bowel disease. Patient counselling is important, but without an associated health literacy assessment to gauge patient understanding, an adequate level of comprehension by the patient may not be reached and health outcomes may be impacted. This may be especially true during the initial office visit, when treatment plans are established. In this study, the rate of counselling was significantly higher than the rate of health literacy assessment in IBD patients. Further research in a larger patient population is necessary to validate these findings. However, performance and documentation of a health literacy assessment during the initial office visit should be encouraged to ensure that patients are engaged in medical discussions and can aid physicians in improving quality of care, health outcomes and patient satisfaction.